REX THE BIG DINOSAUR - "Cartin Morris" (Ladybird Books Ltd UK, 2013)
Rex is a big dinosaur. He sees some small dinosaurs. They are playing. "Can I play, too?" asks Rex. Ladybird Readers is a graded reading series of traditional tales, popular characters, modern stories, and non-fiction, written for young learners of English as a foreign or second language. Beautifully illustrated and carefully written, the series combines the best of Ladybird content with the structured language progression that will help children develop their reading, writing, speaking, listening and critical thinking skills